Extrato aquoso de folhas de pinheira no manejo da casca-preta-do-inhame - Magalhães, Isabelle Cristina Santos (2020)
Yam (Dioscorea spp.) is the fourth most produced tuber crop in the world and its production has been increasing every year due to its excellent acceptance at internal and external markets. Among pests and diseases causing yield losses of yam in Brazil, the most important is the dry rot caused by the plant-parasitic nematodes Scutellonema bradys, Pratylenchus coffeae and P. brachyurus, producing symptoms of tuber necrosis. The present work aimed to evaluate the nematicidal effect of the aqueous extract of Annona squamosa leaves on the management of dry rot of yam in greenhouse conditions. Yam plants were inoculated 30 days after planting with a suspension of 1,000 specimens of S. bradys and Pratylenchus sp., with predominance of the first species. The experiments were performed under a completely randomized design, in a 5 x 2 + 2 factorial scheme, with seven replicates, using five concentrations of custard apple leaf extract (1.0; 2.0; 3.0; 4.0 and 5.0%), two application periods (30 and 60 days after inoculation), plus the negative control (water) and the positive control (Benfurocarbe - Pottente®), where the application of the extract was equivalent to 100 mL per plant. Six months after planting, the population of nematodes in the soil and roots, and the reproduction factor were evaluated. There was no significant difference for the periods of application of the extract in both experiments. Regression analyses were better represented by the root-quadratic model and there was a reduction in the nematode population in all treatments, especially at a concentration of 3%. The aqueous extract of A. squamosa leaves showed a nematicidal effect, being considered efficient in the management of populations of S. bradys and Pratylenchus sp. Key